# 4y=x 3x-y=70

*print*Print*list*Cite

### 9 Answers

This can also be solve using Elimination Method.

Write the first equation in general form: ax + by + c.

Subtract both sides by 4y.

`4y - 4y = x - 4y`

`0 = x - 4y` or `x - 4y = 0`

Let us eliminate the variable x first. To do that, we must make the coefficients of x as additive

inverse of each other. Since we have a 3 as coefficient of x in the second equation, we will make

the coefficient of x in the first equation as -3.

We multiply both sides of the first equation by -3.

`-3(x - 4y) = -3*0`

`-3x+12y = 0`

Apply the Addition Method/Elimination Method now.

`-3x+12y = 0` ``

`+` `3x - y = 70`

_________________

`11y = 70`

Isolate the y on left side by dividing both sides by 11.

`y = 70/11`

Substitute the value of y we got in the first equation.

`4(70/11) = x`

`x = 280/11`

Therefore, the solution set is (280/11,70/11).

That is it! :)

This can be solved by substituting the 4y=x value into the second equation.

3x - y = 70

Replace x with 4y;

3(4y) - y = 70

12y - y = 70

11y = 70

**y = (70/11) or 6.36**

Substituting this into the 4y = x equation;

4(70/11) = x

**(280/11) = x or 25.45**

You can test this by inserting these values into either equation, or by plotting the equations as a graph and finding the intercept.

**Sources:**

4y = x -------eq(i)

3x - y = 70 ----eq(ii)

The value of x and y can be found through the method of substitution, therefore let us consider eq(i)

x = 4y ---eq(i)

Input this value of x in eq(ii)

3x - y = 70 ----eq(ii)

3(4y) - y = 70

12y - y = 70

11y = 70

y = 70/11

Now insert this value in eq(i)

4y = x -------eq(i)

4(70/11) = x

280/11 = x

x = 280/11

Therefore,

**x = 280/11 Answer**

**y = 70/11 Answer.**

Because you know the value of x, you can substitute that into the second equation.

3(4y)-y=70

12y-y=70

11y=70

y=70/11

Now substitute y into the first equation to get x.

4(70/11)=x

x=280/11

First, put 3x-y=70 in standard form: y = 3x -70. Now y is equal to two different equations, therefore if these two equations are equal to y, then they must be equal to each other. Therefore, set the 2 equations equal:

x = 3x-70

Solve for x:

2x = 70

x = 35

4y=x 3x-y=70

substitute 4y for every x

3(4y)-Y=70

12y-y=70

11y=70

y=70/11

then substitute this for y in the smaller equation

4(70/11)=X

280/11 =x:)

4y=x 3x-y=70

3(4y) - y = 70

12y - y = 70

11y = 70

y = 70/11

x = 4(70/11)

x = 280/11

**4y=x **

**3x-y=70**

3(4y) - y =70

12y-y=70

11y=70

**y=70/11**

y= 6.36

**4(70/11)=x**

4y=x

3(4y)-y=70

12y-y=70

11y=70

11y/11=70/11

**y=70/11**

4(70//11)=x

**280/11=x**